PERFORMANCE OF SMALL BUSINESSES: DOES SUSTAINABILITY REPORTING ISSUE MATTER? - Gozali, Efva; Hamzah, Ruth; Ferina, Ika; Annisa, Mutiara; Toruan, Antonius (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Sustainability reporting serves as a valuable tool to demonstrate how a business addresses economic and environmental challenges. This study investigates the influence of age, size and sustainability reporting comprehension of Micro, Small, and Medium-sized Enterprises (MSMEs) on their performance. From a certain population, 40 MSMEs were successfully collected as samples. Logistic regression was employed as the data analysis method. The results reveal that the age do not affect performance, meanwhile size positively affects performance. Moreover, it is found that sustainability reporting comprehension negatively affects performance of MSMEs. The results of this study contribute to bridge the literature gap in the scope of sustainability reporting for MSMEs. In addition, it offers support for the adoption of sustainability reporting standards for MSMEs as a specific sector.